IMPLEMENTASI HUKUM ISLAM TERHADAP PERKAWINAN ANAK DI BAWAH UMUR PADA MASYARAKAT SASAK DI KABUPATEN LOMBOK TENGAH - Made Natalia Supadmi; Made Emy Andayani Citra (Jurnal Hukum Mahasiswa, 2023)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family, therefore marriage is considered something sacred, noble and monumental, underage marriage is an event that is considered normal by some Indonesian people. however, underage marriage can become an issue that attracts public attention and continues to become a legal case, marriage is something that is natural in every human instinct, through marriage humans can maintain the continuity of their lives, marriage is considered one of the phases of life that is almost occurs in every marriage in this thesis research in carrying out marriages in terms of marriage law and child protection has a relationship so that there are no different points of view in its implementation so that the author can review the implementation of Islamic marriage law in legal cases Winan is a minor in the Sasak community in Central Lombok district.